2020
DOI: 10.1101/2020.12.18.20248461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2-Specific Antibody Profiles Distinguish Patients with Moderate from Severe COVID-19

Abstract: SummaryThe production of SARS-CoV-2-specific neutralizing antibodies is widely considered as a key mechanism for COVID-19 resolution and protection. However, beyond their protective function, antibodies to SARS-CoV-2 may also participate in disease pathogenesis. To explore the potential relationship between virus-specific humoral responses and COVID-19 immunopathology, we measured serum antibody classes and subclasses to the receptor-binding domain of the SARS-CoV-2 spike protein and the nucleoprotein in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Additionally, we found that PCs produced many inflammatory factors. Because RBD-specific IgG1 and IgG3 dominate the humoral response against SARS-CoV-2 infection and are positively associated with inflammation (64), future studies should address the roles of metabolic adaptations in PCs in the promotion of IgG1 production and the exacerbation of the disease. In memory B cells, we identified several potential genes related to OXPHOS that may facilitate the differentiation of memory B cells into plasma cells in COVID-19 patients, especially those with severe disease (52).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that PCs produced many inflammatory factors. Because RBD-specific IgG1 and IgG3 dominate the humoral response against SARS-CoV-2 infection and are positively associated with inflammation (64), future studies should address the roles of metabolic adaptations in PCs in the promotion of IgG1 production and the exacerbation of the disease. In memory B cells, we identified several potential genes related to OXPHOS that may facilitate the differentiation of memory B cells into plasma cells in COVID-19 patients, especially those with severe disease (52).…”
Section: Discussionmentioning
confidence: 99%
“…Sera were collected from whole blood, heat-inactivated at 56°C for 1 hour and stored at -20°C prior to use. ELISAs performed in this study were adapted from previously established protocols (21,33). 96-well half-area flat bottom high-bind microplates (Corning) were coated overnight at 4°C with recombinant RBD from SARS-CoV-2 WT or VOCs (a, b g and d) at 2 µg/ml in PBS.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Recent studies have shown that IgG1 and IgG3 subclasses are strongly induced soon after SARS-CoV-2 infection, whereas IgG2 and IgG4 subclasses are induced to a much lesser extent (10,16,21). In recovered individuals, humoral and B cell memory responses appeared to be IgG1-dominated (16,19).…”
Section: Introductionmentioning
confidence: 96%
“…N is the virus nucleocapsid protein, is highly immunogenic and abundantly expressed in vivo after the virus infects human being. S is responsible for binding the virus to the human angiotensin converting enzyme 2 (ACE2) and its subsequent cellular uptake [3][4][5].…”
Section: Antibody Response To Sars-cov-2 Infectionmentioning
confidence: 99%